Jeffrey Fluid Embedded with Dust Particles over a Shrinking Sheet: A Numerical Investigation - Nur Syamilah, Arifin; Syazwani, Mohd Zokri; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; Noor Amalina Nisa, Ariffin (Akademia Baru Publishing (M) Sdn Bhd, 2020)
This study examines the flow behaviour of Jeffrey fluid together with uniform distribution of dust particles that moves over the vertical shrinking sheet. This intriguing mixture employs the two-phase model which mathematically describes the characteristic of both fluid and solid particles in a flow system by a set of partial differential equations. A convenient form of these equations is expressed in the form of ordinary differential equations through the use of similarity transformation and can subsequently be solved by applying the Keller-box method. Numerical solutions for several influencing parameters, namely suction, fluid-particle interaction, magnetic field and aligned angle on the flow and temperature fields of the two components (fluid and dust particles) are presented in graphical form. In addition, the results of skin friction coefficient and Nusselt number at surface of sheet are summarized in the table and analysed in details. It is found that, the velocity and temperature profiles of fluid and dust phases show a similar behaviour in response to all involved parameters except for fluid-particle interaction parameter, respectively.